2014
DOI: 10.1039/c4ra10188j
|View full text |Cite
|
Sign up to set email alerts
|

A styryl-containing aza-BODIPY as a near-infrared dye

Abstract: A novel styryl-containing pyrrole was developed by the reaction of E-4-phenylbut-3-en-2-one with 3-phenyl-2H-azirine in the presence of LDA. Utilizing this pyrrole, asymmetric styryl-containing aza-BODIPYs have been prepared in the NIR region as a result of the extension of conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…A strong bathochromic shift occurs with a change of hydrogen atoms by aryl groups ( Figure 10 ). The absorption bands in the theoretical spectra are underestimated in comparison with the experimental data for A1 – A2 , C1 – C2 [ 35 , 36 , 37 , 38 , 39 ] by ∼64 nm. The observed discrepancy is due to the high multi-reference character of the dipyrrin complexes, as was previously shown by Brown and Momeni [ 40 ].…”
Section: Resultsmentioning
confidence: 66%
“…A strong bathochromic shift occurs with a change of hydrogen atoms by aryl groups ( Figure 10 ). The absorption bands in the theoretical spectra are underestimated in comparison with the experimental data for A1 – A2 , C1 – C2 [ 35 , 36 , 37 , 38 , 39 ] by ∼64 nm. The observed discrepancy is due to the high multi-reference character of the dipyrrin complexes, as was previously shown by Brown and Momeni [ 40 ].…”
Section: Resultsmentioning
confidence: 66%
“…Up to now, these are the only two cases of the non-aryl substituted aza-BODIPY structures so far. 69,70 So, the unique spectral properties and rules of non-aryl substituted aza-BODIPY dyes are still unknown, and the new applications of the functional enhancement are not clear. Our previous work on aza-BODIPYs paved the way to discover non-aryl substituted aza-BODIPYs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, boron difluoride azadipyrromethenes (azaBODIPYs; A in Figure ), as an interesting class of recently developed red to NIR dyes, have received extensive research interest owing to the strong absorption in the NIR region ( λ >650 nm). Several elegant examples, such as thiophene‐substituted azaBODIPYs B , push–pull azaBODIPYs C , and conformationally restricted azaBODIPYs D and E , have been reported that can have further redshifted absorption and emission spectra through structural modifications.…”
Section: Introductionmentioning
confidence: 99%